2011
DOI: 10.1016/s1734-1140(11)70508-4
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between histamine and morphine at the level of the hippocampus in the formalininduced orofacial pain in rats

Abstract: The present study explored the interaction between histaminergic and opioidergic systems at the level of the hippocampus in modulation of orofacial pain by intra-hippocampal microinjections of histamine, pyrilamine (an antagonist of histamine H(1) receptors), ranitidine (an antagonist of histamine H(2) receptors), morphine (an opioid receptor agonist) and naloxone (an opioid receptor antagonist) in separate and combined treatments. Orofacial pain was induced by subcutaneous (sc) injection of formalin (50 μl, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 42 publications
2
32
0
Order By: Relevance
“…Thus, the combinations that enhance opioid analgesic efficacy (e.g., synergism) include association with norepinephrine transport modulators, anti-inflammatory drugs, calcium channels a 2 -d ligands, local anesthetics, a 2 -adrenergic agonists, calcium channel blockers, cannabinoids, GABA B agonists, glial inhibitors, histamine and venlafaxine [4,21,27].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the combinations that enhance opioid analgesic efficacy (e.g., synergism) include association with norepinephrine transport modulators, anti-inflammatory drugs, calcium channels a 2 -d ligands, local anesthetics, a 2 -adrenergic agonists, calcium channel blockers, cannabinoids, GABA B agonists, glial inhibitors, histamine and venlafaxine [4,21,27].…”
Section: Discussionmentioning
confidence: 99%
“…Sensory afferents associated with itch stimulate the histaminergic system in the tuberomammillary nucleus of the hypothalamus [215]. These neurons send axonal projections throughout the CNS.…”
Section: The Physiology and Relevance Of Dry Needling Distal Pointsmentioning
confidence: 99%
“…More specifically, histamine receptors (H1 and H2) have been found in the limbic system, to include the hippocampus, the periaqueductal grey and raphe nuclei [216]. General intracerebralventricular injections and specific microinjections of histamine into the periaqueductal grey and raphe nuclei all had antinociceptive effects in animal models [215]. Tamaddonfard et al further demonstrated a synergistic effect of morphine and histamine in the hippocampus [215].…”
Section: The Physiology and Relevance Of Dry Needling Distal Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that opioid system, through mu, delta, and kappa receptors, mediates local peripheral, spinal, and supraspinal mechanisms of pain and analgesia (Kanjhan 1995;Stein and Zollner 2009;Bodnar 2014). Using naloxone, some researchers have suggested possible interactions between histamine and opioid systems in supraspinal modulation of pain and analgesia (Tamaddonfard et al 2011;Tamaddonfard and Hamzeh-Gooshchi 2014;Hamzeh-Gooshchi et al 2015).…”
Section: Introductionmentioning
confidence: 99%